External audit quality and employee efficiency: A bibliometric analysis - Lukman, Jimoh, Adams; Durodolu, Oluwole O. (Edelweiss Applied Science and Technology, 2026)
The increasing complexity of corporate operations, digital reporting, and cross-border transactions has heightened the importance of external audit quality as a pillar of accountability and capital market trust. While prior research links audit quality to earnings management, reporting credibility, and investor protection, its impact on employee effectiveness remains underexplored. This study addresses that gap through a systematic literature review of 2020–2026 publications, integrating auditing and workforce performance research using a PRISMA-guided approach and bibliometric analysis. Eighty peer-reviewed studies from Scopus, Web of Science, Google Scholar, and local repositories were analyzed. VOSviewer mapped co-citation networks, keyword co-occurrence, and bibliographic coupling to identify the field’s intellectual structure. Findings suggest an emerging link between high audit quality and employee effectiveness through stronger monitoring, standardized controls, and signaling effects that enhance discipline and productivity. However, conceptual fragmentation persists in measuring employee effectiveness and in addressing digital and ESG-related audit dynamics. High-quality external audits enhance governance, reporting credibility, accountability, and employee effectiveness through stronger monitoring and standardized controls. Organizations should improve auditor independence, expertise, and oversight to strengthen productivity and discipline.